A procedure to select ground-motion time histories for deterministic seismic hazard analysis from the Next Generation Attenuation (NGA) database - Huang, Duruo (2018)
In performance-based seismic design, ground-motion time histories are needed for analyzing dynamic responses of nonlinear structural systems. However, the number of ground-motion data at design level is often limited. In order to analyze seismic performance of structures, ground-motion time histories need to be either selected from recorded strong-motion database or numerically simulated using stochastic approaches. In this paper, a detailed procedure to select proper acceleration time histories from the Next Generation Attenuation (NGA) database for several cities in Taiwan is presented. Target response spectra are initially determined based on a local ground-motion prediction equation under representative deterministic seismic hazard analyses. Then several suites of ground motions are selected for these cities using the Design Ground Motion Library (DGML), a recently proposed interactive ground-motion selection tool. The selected time histories are representatives of the regional seismic hazard and should be beneficial to earthquake studies when comprehensive seismic hazard assessments and site investigations are unavailable. Note that this method is also applicable to site-specific motion selections with the target spectra near the ground surface considering the site effect.